2015
DOI: 10.1515/plc-2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Trajectory of Audiovisual Speech Integration in Early Infancy. A Review of Studies Using the McGurk Paradigm

Abstract: Apart from their remarkable phonological skills young infants prior to their fi rst birthday show ability to match the mouth articulation they see with the speech sounds they hear. Th ey are able to detect the audiovisual confl ict of speech and to selectively att end to articulating mouth depending on audiovisual congruency. Early audiovisual speech processing is an important aspect of language development, related not only to phonological knowledge, but also to language production during subsequent years. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 133 publications
0
10
0
Order By: Relevance
“…Although a growing body of evidence demonstrates that substantial fine-tuning for various forms of audiovisual processing continues throughout childhood and well into adolescence (Baart et al, 2015 ; Tomalski, 2015 ), suffice it to say that at least some primitive form of multimodal perception emerges in early infancy (Bahrick et al, 2004 ). This can be characterized as guided by both modal cues (i.e., those that are specific to a single modality, such as color information in the visual domain or the timbre of someone's voice in the auditory domain) and amodal ones (i.e., those that are available across modalities and are thus redundant; Bahrick, 1988 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although a growing body of evidence demonstrates that substantial fine-tuning for various forms of audiovisual processing continues throughout childhood and well into adolescence (Baart et al, 2015 ; Tomalski, 2015 ), suffice it to say that at least some primitive form of multimodal perception emerges in early infancy (Bahrick et al, 2004 ). This can be characterized as guided by both modal cues (i.e., those that are specific to a single modality, such as color information in the visual domain or the timbre of someone's voice in the auditory domain) and amodal ones (i.e., those that are available across modalities and are thus redundant; Bahrick, 1988 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hick et al [34] concluded from their work that SLI children demonstrated slower development of the short term memory. Tomalski [35] reported that human speech is a multisensory experience and the most important modalities for language comprehension and production are visual spatial modalities. They reported that integrity of the social pragmatics aspects resulted from adequacy of audiovisual processing of the speech.…”
Section: Assessment Of Visual Working Memory (Wm)mentioning
confidence: 99%
“…Several studies with infants as young as four months found that their pattern of illusory phoneme detection was similar to that of adults [13,28]. However, other studies have found different results in male and female infants depending on the experimental design [29,30], showing that the effect is not as strong or consistent as in adults. Therefore, the literature suggests that infants are sensitive to cases of temporal and phonological audiovisual synchrony, suggesting a possible innate audiovisual integration skill.…”
Section: Introductionmentioning
confidence: 99%